Clinical and laboratory evaluation of lymphadenopathy in particular with fine needle aspiration cytology - K., Nageshwara Rao; Gopal, Harisha; M., Gautham (International Journal of Contemporary Pediatrics, 2019)
Background: To know the various causes of lymphadenopathy in children and to know the usefulness of FNAC in diagnosis of various causes of lymphadenopathy. Methods: Children less than 12 years with significant lymphadenopathy (lymphadenopathy of >1 cm in cervical, axillary and >1.5 cm in inguinal region) were included. Results: A total of 50 children were enrolled in the study. The incidence of lymphadenopathy was more common in the age group of 4-8 year during the lymphoid phase with male preponderance of all the causes infections especially tuberculosis was the major cause of lymphadenopathy which is totally preventable by giving BCG vaccination. The sensitivity of FNAC in the present study was 71.3%. In 3 cases FNAC 69 was not done because peripheral smear examination revealed that the patients are suffering from acute lymphoblastic leukemia. Conclusions: FNAC is a simple bed side investigation though traumatic is of immense value for diagnosing various cases. Even though it may not be a replacement for lymphnode biopsy, it is preferred as a first line investigation because of its simple procedure.